Effects of fertilizer on inorganic soil N in East Africa maize systems: vertical distributions and temporal dynamics. Issue 6 (2nd September 2016) - Tully, Katherine L.; Hickman, Jonathan; McKenna, Madeline; Neill, Christopher; Palm, Cheryl A.
Abstract: Fertilizer applications are poised to increase across sub‐Saharan Africa (SSA), but the fate of added nitrogen (N) is largely unknown. We measured vertical distributions and temporal variations of soil inorganic N following fertilizer application in two maize ( Zea mays L .)‐growing regions of contrasting soil type. Fertilizer trials were established on a clayey soil in Yala, Kenya, and on a sandy soil in Tumbi, Tanzania, with application rates of 0–200 kg N/ha/yr. Soil profiles were collected (0–400 cm) annually (for three years in Yala and two years in Tumbi) to examine changes in inorganic N pools. Topsoils (0–15 cm) were collected every 3–6 weeks to determine how precipitation and fertilizer management influenced plant‐available soil N. Fertilizer management altered soil inorganic N, and there were large differences between sites that were consistent with differences in soil texture. Initial soil N pools were larger in Yala than Tumbi (240 vs. 79 kg/ha). Inorganic N pools did not change in Yala (277 kg/ha), but increased fourfold after cultivation and fertilization in Tumbi (371 kg/ha). Intra‐annual variability in NO − 3 ‐N concentrations (3–33 μg/g) in Tumbi topsoils strongly suggested that the sandier soils were prone to high leaching losses. Information on soil inorganic N pools and movement through soil profiles can h vulnerability of SSA croplands to N losses and determine best fertilizer management practices as N application rates increase. A better understanding of the vertical and temporal patterns of soil N pools improves our ability to predict the potential environmental effects of a dramatic increase in fertilizer application rates that will accompany the intensification of African croplands.